PRELIB, base de données sur les acteurs du domaine littéraire en langue bretonne - Nelly Blanchard; Jean-Baptiste Pressac; Mannaig Thomas (Lengas)
PRELIB is a database on actors in the Breton-language literary field. Among other things, it makes it possible to identify the places of sociability and networks in which these actors operate, based on quantitative and graphically visualizable data on their social and literary trajectories. Its production raises epistemological questions about what a work or an interpersonal relationship is, reflections that this article proposes to expose. Hkjhkhmlkhk